New records of mushrooms for the mycobiota of Azerbaijan - Mustafabayli, E.H.; Aghayeva, D.N. (Український ботанічний журнал, 2019)
The article reports data on 24 new records of mushrooms in Azerbaijan. Fungal specimens were collected during 2014– 2018 in Shaki District of Azerbaijan. These are Auriscalpium vulgare, Boletus aereus, B. edulis, B. variipes, Caloboletus radicans, Calocybe gambosa, Cantharellus subalbidus, Clavariadelphus pistillaris, Cortinarius triumphans, Hemileccinum depilatum, Hortiboletus rubellus, Hydnellum concrescens, Inonotus obliquus, Marasmius capillaries, Phaeomarasmius erinaceus, Phallus ravenelii, Ramaria obtusissima, Rheubabariboletus armeniacus, Rubroboletus legaliae, R. lupinus, R. satanas, Russula turci, Suillus collinitus, and Tremella mesenterica. For each specimen, its locality, biotope and collection data are indicated and photographs are provided.